Should acupuncture become a complementary therapy in the treatment of uterine fibroid: a systematic review and meta-analysis of randomized controlled trials - Ren, Yuehan; Zhang, Junning; Wu, Weizhen; Yuan, Yi; Wang, Jiale; Tang, Yi; Liao, Yan; Liu, Xinmin (Frontiers in Medicine, 2023)
Background Uterine fibroids (UFs) are the most common benign tumors in women of reproductive age. The most effective treatment is myomectomy, but there's no long-term or lowinvasive treatment option exists. Acupuncture can be used to treat UFs in a variety of ways. However, there is no meta-analytic synthesis including valid data that explored the efficacy of acupuncture for UFs.Objective To assess the efficacy and safety of acupuncture for treating UFs.Methods The PRISMA 2020 checklist was used. we identified and extracted the trials through May 2023 from six databases. The quality of the trials was assessed using the Risk of Bias (2.0). Meta-analysis was performed using RevMan 5.4 software, and it was synthesized using the random-effects model if the included studies were in high heterogeneity. Subgroup and sensitivity analysis were used if necessary.Results A total of 1035 trials were identified, of which 11 were included in the review and metaanalysis. In terms of acupuncture scheme design and fibroid-related symptoms, the trials are highly heterogeneous. All 11 trials have reported acupuncture types, with traditional acupuncture and electroacupuncture being the more representative subgroups. A qualitative review of existing evidence shows that acupuncture has no serious adverse reaction on UFs. Meta-analysis shows that acupuncture can effectively reduce the volume of UFs(MD -3.89, 95% CI -5.23 to -2.56, p < 0.00001) or uterine volume(MD -16.22, 95% CI -19.89 to -12.55, p < 0.00001), reduce the score of fibroid symptoms(MD -3.03, 95% CI − 3.45 to -2.60, p < 0.00001), improve the treatment efficiency(RR: 0.19, 95% CI: 0.13 to 0.25, p < 0.00001), and likely do not affect the estrogen level.